2021
DOI: 10.3390/jmmp5010015
|View full text |Cite
|
Sign up to set email alerts
|

Die Material Selection Criteria for Aluminum Hot Stamping

Abstract: The aim of this work is to develop a die material selection criterion for aluminum hot stamping applications. The criterion has been based on the back-to-back comparison of a set of reciprocating friction and wear tests. Three representatives belonging to different stamping die material families have been selected for the study: a cold work steel, a hot work steel, and a cast iron. These tool materials have been combined with an exemplary member from two heat treatable aluminum families: 2XXX and 6XXX. Each di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Its tensile strength can reach 1200~2000 MPa. Compared with other lightweight materials such as aluminum alloys, hot-stamped steel materials have the advantages of controllable manufacture-use-maintenance cost, good processability, and good lightweight potential, and thereby the proportion of applications is increasing in the automobile field [12][13][14][15][16][17][18][19]. The application of hot-stamped steels as a structural part of the body in white (BIW) can reduce the weight and ensure safety performance.…”
Section: Introductionmentioning
confidence: 99%
“…Its tensile strength can reach 1200~2000 MPa. Compared with other lightweight materials such as aluminum alloys, hot-stamped steel materials have the advantages of controllable manufacture-use-maintenance cost, good processability, and good lightweight potential, and thereby the proportion of applications is increasing in the automobile field [12][13][14][15][16][17][18][19]. The application of hot-stamped steels as a structural part of the body in white (BIW) can reduce the weight and ensure safety performance.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the matrix material has a significant impact on the extrusion process. Muro et al [ 10 ] showed the influence of the matrix material in the hot stamping process on the process of its wear. Terčelj and Kugler [ 11 ] pointed out that optimizing geometry and technological parameters allows the life of matrices to be extended.…”
Section: Introductionmentioning
confidence: 99%